2020
DOI: 10.1007/s11071-020-05639-x
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous whirling of spinning homogeneous elastic cylinders: linear and weakly nonlinear analyses

Abstract: Stationary whirling of slender and homogeneous (continuous) elastic shafts rotating around their axis, with pin-pin boundary condition at the ends, is revisited by considering the complete deformations in the cross section of the shaft. The stability against a synchronous sinusoidal disturbance of any wave length is investigated and the analytic expression of the buckling amplitude is derived in the weakly non-linear regime by considering both geometric and material (hyper-elastic) non-linearities. The bifurca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…When subjected to centrifugal forces, these soft solids can undergo deformation and buckling instability. [ 95–100 ] In the case of a disk, it has been observed that the deformation and buckling are most pronounced near its inner edge ( Figure a). Studies shown that increasing the rotating speed not only shifts the buckling deformation toward the inner edge of the disk but also increases the wavenumber of the buckling.…”
Section: Gravity‐induced Instabilities In Soft Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…When subjected to centrifugal forces, these soft solids can undergo deformation and buckling instability. [ 95–100 ] In the case of a disk, it has been observed that the deformation and buckling are most pronounced near its inner edge ( Figure a). Studies shown that increasing the rotating speed not only shifts the buckling deformation toward the inner edge of the disk but also increases the wavenumber of the buckling.…”
Section: Gravity‐induced Instabilities In Soft Materialsmentioning
confidence: 99%
“…On the other hand, for a solid cylinder, increasing the rotating speed does not alter the buckling mode but results in an increase in the buckling amplitudes (Figure 7b). [ 98 ] This suggests that higher rotational speeds primarily affect the magnitude of the buckling deformation in the cylinder while maintaining the same mode of buckling. The understanding of the mechanical behavior of rotating soft solids is crucial in various applications.…”
Section: Gravity‐induced Instabilities In Soft Materialsmentioning
confidence: 99%
See 1 more Smart Citation